Link between neurodevelopmental disorders and suicidal risk in children - Lévy-Bencheton, Julie; Chaste, Pauline; Sansen, Mélisande (Encéphale, 2025)
Suicide represents a significant public health issue among children and adolescents. However, in this population, while the literature seems to support a link between suicidal risk and neurodevelopmental disorders, there are still few studies on the subject. The psychopathological description of children who have realized a suicide attempt with a high potential for lethality, which can be defined as "serious", appears to resemble that of children who have died by suicide. This study aimed to characterize the dimensional aspects of the neurodevelopmental profile of a population of children and adolescents hospitalized at Necker-Enfants-Malades Hospital for a serious suicide attempt. This is an observational, prospective, and single-center study. Questionnaires for collecting general information and dimensional scales of neurodevelopment (Autism-Tics, ADHD, and Other Comorbidities Inventory, Social Responsiveness Scale, and Conners-3 for parents) were used. This study included 21 patients aged 9 to 15 years at the time of their hospitalization. The results supported the presence of at least one neurodevelopmental disorder (autistic traits, attention-deficit/hyperactivity disorder, learning disorder, or motor disorder) in 70% (n=14) of the subjects, and at least one behavioral disorder (oppositional defiant disorder, conduct disorder) in 65% (n=13) of these subjects. The observed frequency of traits indicative of neurodevelopmental disorders in our population was higher than that observed in the general population, without the presented symptoms being eligible for categorical diagnosis. Considering the dimensional aspects of neurodevelopmental symptoms would therefore enable better identification of children at suicidal risk and more tailored interventions to contribute to the prevention of suicide in children.